Complex Care Curriculum: Palliative Care for the Medically Complex Child - Melanie Anspacher; Neha Shah (Association of American Medical Colleges, 2013)
Abstract Introduction Children with special health care needs are increasingly prevalent in US hospitals. The pediatric hospitalist is often the primary provider of inpatient care for these patients. The Complex Care Curriculum was developed to provide a multi-modal educational curriculum for providers with the overall goal of improving inpatient care for this population. The curriculum is composed primarily of a series of topic-specific learning modules. Methods This particular resource was created to provide pediatricians with educational materials related to palliative care for the medically complex child. This resource includes a multimedia, narrated PowerPoint presentation for asynchronous learning, a PowerPoint presentation adapted for didactic teaching, as well as accompanying facilitator guides, suggested multiple-choice questions with answer key, an evaluation tool, and a complete list of references and resources. The target audience is pediatric hospitalists and other general pediatric providers or trainees who care for medically complex children in an inpatient setting, although it may also be applicable to health care providers in outpatient settings. This resource can be used to study independently or to teach to other learners in small group settings. Results This module was created as part of a larger Complex Care Curriculum by authors in the Pediatric Hospitalist Division at Children's National Medical Center in Washington, DC. It was implemented in 2012 and a pilot study of participants was conducted. Fifteen study participants completed the palliative care module. Of these participants, 93% either agreed or strongly agreed that the module increased their comfort with the topic and that it would change their clinical practice. All agreed that the learning format was appropriate to their learning needs. Results of the pilot study showed a statistically significant increase in test scores on the palliative care questions specifically. Comments from participants on this learning module included: "Material was well organized," "The case really centered the topic," "Excellent overview and enjoyed specific case references," "Academic references were appreciated," "Covered highlights of what should be known by the general hospital pediatrician." Discussion Based on this study, this module along with others in the curriculum continues to be offered to trainees and new faculty to augment their knowledge and skills in this area.